Proses Olah Vokal Dalang Perempuan (The Process Of Female Puppeteers’ Vocalism) - Anisyah Padmanila Sari (Wayang Nusantara: Journal of Puppetry, 2020)
AbstrackThis paper aims to describe the vocal processing of six female puppeteers who are the object of research. This description is intended to give an idea of how they practice and what methods are used in vocal processing by each puppeteer. Based on the results of interviews, observations, and directly following their activities as a female puppeteer, it was concluded that the votes obtained now are the result of regular, continuous training over a long period of time. The process of vocal processing by ninthing gendèr and spiritual behavior is passed by all female puppeteers. There are two interesting things to note are (1) a female puppeteer who wants her voice to approach a male voice trains her voice in order to reach the notes in the lower octaves and become gérong; (2) a female puppeteer who remain with their female voices put more emphasis on ninthing gendèr and breathing exercises. AbstrakTulisan ini bertujuan mendeskripsikan proses olah suara enam dalang perempuan yang menjadi obyek penelitian. Deskripsi ini dimaksudkan untuk memberi gambaran tentang bagaimana mereka berlatih dan metode apa yang digunakan dalam berolah suara oleh masing-masing dalang. Berdasarkan hasil wawancara, pengamatan, dan mengikuti secara langsung kegiatan mereka sebagai dalang perempuan, diperoleh kesimpulan bahwa suara yang didapat sekarang merupakan hasil latihan secara rutin, terus-menerus dalam waktu yang cukup panjang. Proses olah suara dengan ninthing gendèr dan laku spiritual dilalui oleh semua dalang perempuan. Ada dua hal yang menarik untuk diperhatikan ialah (1) dalang perempuan yang ingin suaranya mendekati suara laki-laki melatih suaranya agar dapat mencapai nada-nada pada oktaf rendah dan menjadi gérong; (2) dalang perempuan yang tetap dengan suara perempuannya lebih menekankan pada latihan ninthing gendèr dan latihan pernafasan.